PM10-Bound Sugars: Chemical Composition, Sources and Seasonal Variations - Gonçalves, Cátia (2021)
The presence of anhydrosugars and sugar alcohols in airborne articulate matter <10 m (PM10) samples collected between December 2018 and June 2019 was studied for two urban environments in Coimbra. Anhydrosugars were used to estimate the biomass burning contribution, and sugar alcohols were investigated regarding biological sources. Anhydrosugars contributed more than sugar alcohols to the total sugars, mainly levoglucosan. Higher levoglucosan concentrations were linked with the use of biomass-fueled heating appliances, mainly during cold periods. A significant contribution from biomass burning smoke was registered, accounting for 20% to 23% of the PM10 mass in the colder period. Xylitol presented higher concentrations in the colder period and was well correlated with levoglucosan, indicating a common origin. Mannitol and arabitol were well correlated with each other but did not present any kind of correlation with anhydrosugars or xylitol, suggesting a natural source. A quantitative estimation based on the concentration of ambient tracers (mannitol) was evaluated, and the results reveal that, for the two sites, the fungal spore relative contribution to PM10 (roadside site: 2.7% to 2.8%; urban background: 1.9% to 2.7%) and OC mass (roadside site: 6.2% to 8.1%; urban background: 3.9% to 7.5%) was significant and always higher in the warmer period.